2020
DOI: 10.1111/nicc.12539
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheters misplaced in paraspinal veins: A systematic literature review based on case reports

Abstract: Background: Paraspinal vein misplacement is an uncommon complication of central venous catheterization via lower extremities, most of which have been reported in case reports.Aim: To determine the clinical characteristics of paraspinal vein misplacement.Design: This was a systematic review.Methods: A systematic literature search in the PubMed, EMBASE, Scopus, and Web of Science databases was performed from their inception to 18 June 2019. Case reports and small case series describing central venous catheter mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In a 1997 study, Durbec et al 19 reported a primary tip’s malposition rate of 37%. In particular, tip’s positioning in the paraspinal veins represents one of the situations which, although little investigated in the literature, 20 appears to be burdened by several consequences, 21 including clinical complications (76.2%) and death (26.9%). According to the need to reach an efficient control of the tip’s position in a bedside setting, in which no standard real time tip’s location procedure is reported in literature, we chose to rely only on ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…In a 1997 study, Durbec et al 19 reported a primary tip’s malposition rate of 37%. In particular, tip’s positioning in the paraspinal veins represents one of the situations which, although little investigated in the literature, 20 appears to be burdened by several consequences, 21 including clinical complications (76.2%) and death (26.9%). According to the need to reach an efficient control of the tip’s position in a bedside setting, in which no standard real time tip’s location procedure is reported in literature, we chose to rely only on ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Although the position of the catheter tip inserted through the femoral vein is often confirmed on a frontal abdominal radio-graph, complications can arise if the catheter is misplaced into branching veins that are not identified by radiographs. Catheters inserted from the left femoral vein have been reported to stray into the left lumbar vein, whereas catheters inserted from the right femoral vein are less frequently misplaced into the right lumbar vein [ 6 ]. In this report, we present a case in which a catheter tip accidentally strayed into the right ascending lumbar vein during catheter insertion from the right femoral vein, and this misplacement was not detected on a frontal abdominal radiograph.…”
Section: Introductionmentioning
confidence: 99%
“…10 This survey was undertaken to examine the reasons for the comparatively high incidence of restraint use in Turkey 11 The next paper in this issue presents a systematic review of case reports and case series of the uncommon but potentially fatal misplacement of central venous catheters in paraspinal veins. 12 The aim of this review was to describe the clinical characteristics of this complication. This knowledge is essential for nurses caring for patients who have central venous catheters placed in lower extremities, especially in paediatrics where this occurs most commonly.…”
mentioning
confidence: 99%